Pharmacological Management of Esophageal Food Bolus Impaction - Yasir Mohammed Khayyat (Emergency Medicine International)
Background. Soft esophageal bolus impaction is an emergency that requires skilled endoscopic removal if persistent obstructive symptoms do not resolve spontaneously after careful observation. Expedited care of these patients is crucial to avoid respiratory and mechanical complications. Other possible options for management include medical agents used to manage it prior to performing endoscopy if access to endoscopy was not available or declined by the patient. Aim. To review the available pharmacological and other nonmedicinal options and their mechanism of relief for soft esophageal impaction. Method. Pubmed, Medline and Ovid were used for search of MESH terms pertinent including “foreign body, esophageal, esophageal bolus and medical” for pharmacological and non medicinial agents used for management of esophageal soft bolus impaction as well as manual review of the cross-references. Results. Several agents were identified including Buscopan, Glucagon, nitrates, calcium channel blockers, and papaveretum. Non medicinal agents are water, effervescent agents, and papain. No evidence was found to suggest preference or effectiveness of use of a certain pharmacological agent compared to others. Buscopan, Glucagon, benzodiazepines, and nitrates were studied extensively and may be used in selected patients with caution. Use of papain is obsolete in management of soft bolus impaction.